The Environmental, Social and Governance Aspects of Social Responsibility Indices – A Comparative Analysis of European SRI Indices - Mikołajek-Gocejna, Magdalena (Comparative Economic Research. Central and Eastern Europe, 2018)
An increasing number of investors want to invest their capital not only with profit but also responsibly, and they pay significant attention to the formula of socially responsible investing (SRI), which means that they consciously engage their funds in companies operating in accordance with CSR principles. An important influence on the development of CSR is the role of stock exchange indices on socially responsible companies. These indices can be considered specific tools for adapting this concept in practice, in particular in the field of socially responsible investment. This article provides a comparative analysis of the social, environmental and governance criteria underlying the definition of the composition of selected European SRI indices. The research will cover the following indices: the DJSI Europe Index, the FTSE4Good Europe 40, the FTSE4Good Europe 50, the EURO STOXX Sustainability 40 and the Solactive Sustainability Index Europe. This paper also intends to set an index reflecting the degree to which companies of certain European countries are represented in major European SRI indices. Consequently, global and national initiatives and ratings were excluded, as well as sector‑and industry‑specific initiatives and ratings. The proposed index is standardized by introducing the GDP of each country into the calculation formula as a way to a achieve comparable result. We believe that the proposed metric will reflect the state of the art in SRI and provide an overall picture of SRI practices across nations.